PENGENDALIAN MUTU PEMBANGUNAN RUMAH SAKIT DI MOJOKERTO PROVINSI JAWA TIMUR - Romy Fansuri Yahya; Sumardi; Dandung Novianto (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2019)
The project was undertaken by CV. Dwi Mulya Jaya with the contract price of IDR. 9,431,000,000.00 on 150 calendar days. An alternative project planning was in need to complete the project on time, cost, and qualityThe project planning included; 1) site layout; 2) traffic managemnet; 3) implementation method; 4) scheduling; 5) cost; 6) quality and 7) safety.Technical drawings, technical specifications, bill of quantity, and work unit price of Mojokerto 2016 were needed. Microsoft Exel 2013 and Microsoft Project 2007 were employed to determine the project price and scheduling.The planning results in: 1) direction kit in the front of the project, on the right side; 2) one-gate system; 3) two-zone system and cast-in-situ method; 4) on 147 calendar days; 5) at IDR 8,188,864,607.06; 6) the quality meeting the specification and Standard Operational Procedure; 7) applying safety rules on Mondays. Keywords: project planning, site layout, implementation method.